"India's global powerhouses: how they are taking on the world / by Nirmala Kumar, Pradipta K. Mohapatra and Suj rasekhar" - "Kumar, Nirmalya" (Boston, 1950)
When the Indian auto manufacturer Tata Motors bought the iconic Jaguar and Land Rover brands - complementing the Nano, its own innovative $2, 500 car - it opened up a new chapter in India's economic story. In the coming years, such Indian multinationals as Bharat Forge, Hidalgo, Infosys, Mahindra and Salon will increasingly be making acquisitions and building their brands in Western markets. Never heard of them? Then read this book. India's Global Powerhouses introduces you to the India's preeminent global companies and explains how they differ from their international rivals. The book profiles India's pioneering multinationals in detail, describing their transformation from leading domestic players to evolving global giants, as well as their unique approaches to globalization. Every manager should understand the histories and the business trajectories of these prospective competitors, collaborators and customers - whose names will soon be as familiar to us as Honda, Lenovo and Samsung. Normally Kumar has captured the energy and the ambition driving those Indian companies that have become globule powerhouse. When India opened to the world in 1991, few imagined that there company would go global. This book documents their remarkable success.
Keywords: International business enterprises-India